2018
DOI: 10.1108/ejm-12-2016-0727
|View full text |Cite
|
Sign up to set email alerts
|

The application of mobile fNIRS to “shopper neuroscience” – first insights from a merchandising communication study

Abstract: Purpose This study is the first to examine consumer’s neural reaction to different merchandising communication strategies at the point-of-sale (PoS) by applying functional near-infrared spectroscopy (fNIRS). By doing so, the purpose of this study is to extend consumer neuroscience to retail and shopper research. Design/methodology/approach Two experiments were conducted in which 36 shoppers were exposed to a realistic grocery shopping scenario while their brain haemodynamics were measured using mobile fNIRS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 72 publications
1
53
0
1
Order By: Relevance
“…[35], Gordon et al [59], Krampe et al [60], Hubert et al [25], Çakir et al [24], Holst and Henseler [61], Hsu and Cheng [62], Hoefer et al [27], Chen et al [49], Casado-Aranda et al [50], Wang et al [30], Jain et al [63], Wolfe et al [31], Bosshard et al [32], Fehse et al [33].…”
Section: Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35], Gordon et al [59], Krampe et al [60], Hubert et al [25], Çakir et al [24], Holst and Henseler [61], Hsu and Cheng [62], Hoefer et al [27], Chen et al [49], Casado-Aranda et al [50], Wang et al [30], Jain et al [63], Wolfe et al [31], Bosshard et al [32], Fehse et al [33].…”
Section: Promotionmentioning
confidence: 99%
“…Functional near-infrared spectroscopy (fNIRS) is another new brain imaging tool which uses the hemodynamic responses associated with neuronal activities [24,60]. However, fNIRS has a lower spatial resolution than fMRI and cannot look deeper than 4 cm.…”
Section: Activation Of Brain Regions Due To Marketing Stimulimentioning
confidence: 99%
“…Indeed, NIRS is small and discreet enough to be incorporated in a hat, and advances in wireless technology mean that real-time transmission of data is already possible from the majority of consumer locations. Using fNIRS, Krampe et al (2018) devised an experimental paradigm where participants viewed first-person video footage of supermarket aisles with and without merchandising communications. The study observed differential activity in the prefrontal cortex, specifically the orbitofrontal cortex and dorsolateral prefrontal cortex when comparing communication strategies, demonstrating the sensitivity of the technology for observing consumer neural activity.…”
Section: Physiological and Neuroscientific Measures Used In Consumer mentioning
confidence: 99%
“…This is also relevant for the data analysis of fNIRS experiments conducted in the field, as it takes significantly more time and effort to analyse the data as the stimuli onsets have to be defined ex post and with the help of another neurophysiological methods such as e.g., eye-tracking. Nevertheless, based on our research work and recent research findings (Krampe et al, 2018a , b ), it should be evident that the advantages of conducting mobile fNIRS experiment may exceed potential disadvantages.…”
Section: Mobile Fnirs—a Short Guideline For Marketing Researchmentioning
confidence: 55%